2015
DOI: 10.1016/j.ijnss.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on experience of nurses caring for patients with delirium in ICUs in China: Barriers, burdens and decision making dilemmas

Abstract: Purpose:The purpose was to explore the experiences of nurses caring for patients with delirium in ICU in China.Methods: Semi-structured qualitative interviews were conducted with 14 ICU nurses in Beijing, China. Audio recordings of the transcripts were coded and analyzed thematically. Results:The emergent themes reflected clearly similar experiences and were titled as follows: Internal and external barriers to care; Care burden: workload, psychological pressure and injury; Dilemmas in decision-making: balancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 32 publications
5
37
0
4
Order By: Relevance
“…This finding was similar to the study conducted in Jordan by Hamdan-Mansour et al 2 and Yue et al 8 Another study suggested that comprehensive educational programs were needed to decrease accident related to ICU syndrome and to improve the health of ICU patients.…”
supporting
confidence: 90%
“…This finding was similar to the study conducted in Jordan by Hamdan-Mansour et al 2 and Yue et al 8 Another study suggested that comprehensive educational programs were needed to decrease accident related to ICU syndrome and to improve the health of ICU patients.…”
supporting
confidence: 90%
“…Patients with hyperactive delirium are unpopular amongst nurses (Williams, ). Failure to engage with delirious patients may stem from the challenge these patients present to the bedside nurse (Mc Donnell & Timmins, ; Yue, Wang, Liu, & Wu, ; Zamoscik et al, ). Staff report experiences of emotional and physical exhaustion stemming from caring for delirious patients, especially over long shifts (Yue et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Yue, et al, [20] who stated lack of knowledge and skills required to assess and manage the delirium patients lead to preventing nurses from recognizing early symptoms. As well as Trogrlic et al, [21] who made a survey among intensive care unit professionals about their attitude, knowledge and practices concerning delirium, the study indicated that knowledge deficit were presented more clearly in nurses than in physicians.…”
Section: Discussionmentioning
confidence: 99%
“…This results contradicted with [21] who founded that The majority of the respondents were frequently performed promotion of day time wakefulness (81%), use of glasses when patients are visually impaired (74%) and use of hearing aids when patients are hearing impaired (67%). However, Yue et al, [20] explained unsatisfactory delirium practice from the side of nurses resulting from the lack of knowledge, absence of evidence-based nursing practice, complex symptoms, and changing shifts which leads to difficulties in detecting the early delirium signs.…”
Section: Discussionmentioning
confidence: 99%